2005
DOI: 10.1038/nature03232
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and validation of modelled sphingolipid metabolism in Saccharomyces cerevisiae

Abstract: Mathematical models have become a necessary tool for organizing the rapidly increasing amounts of large-scale data on biochemical pathways and for advanced evaluation of their structure and regulation. Most of these models have addressed specific pathways using either stoichiometric or flux-balance analysis, or fully kinetic Michaelis-Menten representations, metabolic control analysis, or biochemical systems theory. So far, the predictions of kinetic models have rarely been tested using direct experimentation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
135
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 146 publications
(136 citation statements)
references
References 21 publications
1
135
0
Order By: Relevance
“…By monitoring the absolute abundance of individual lipid species we demonstrated that differences in growth temperature and defects in the lipid biosynthesis machinery produced alterations throughout the entire yeast lipidome. These ripple effects could not have been predicted from known activities of lipid biosynthesis enzymes (32). We also note that phenotypes seen upon deletion of genes expected to affect a specific lipid class might derive from seemingly unrelated compensatory changes within the lipidome that can only be assessed by global lipid analysis.…”
Section: Discussionmentioning
confidence: 99%
“…By monitoring the absolute abundance of individual lipid species we demonstrated that differences in growth temperature and defects in the lipid biosynthesis machinery produced alterations throughout the entire yeast lipidome. These ripple effects could not have been predicted from known activities of lipid biosynthesis enzymes (32). We also note that phenotypes seen upon deletion of genes expected to affect a specific lipid class might derive from seemingly unrelated compensatory changes within the lipidome that can only be assessed by global lipid analysis.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been known that inositol-containing sphingolipid synthesis is reduced during inositol starvation (13,(53)(54)(55). It has also been shown that treating cells with AbA (56) inhibits inositol phosphorylceramide synthase activity leading to a reduction in inositol-containing sphingolipid synthesis (57).…”
Section: Discussionmentioning
confidence: 99%
“…The signals, which result from inositol and/or lipid metabolism and control the responses of genes other than those containing the UAS INO element (2), remain to be elucidated. In yeast, PI also serves as a precursor to the inositol-containing sphingolipids, which have also been shown to undergo changes in metabolism following inositol addition (47). In yeast, PI also serves as precursor to phosphoinositides, as well as a variety of inositol phosphates, many of which play roles in transcriptional regulation signaling processes and membrane trafficking (36).…”
Section: Discussionmentioning
confidence: 99%